Effectiveness of azithromycin and ciprofloxacin in the treatment of typhoid fever: a systematic review - Mulyono, Bethea Manuela; Ita Margaretha Nainggolan; Linawati Hananta; Lucky Hartati Moehario (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
Typhoid fever or commonly referred to as enteric fever is a systemic disease caused by Salmonella typhi. It often occurs in developing countries due to poor sanitation. Second-line antibiotics, including ciprofloxacin, have been widely used as the first choice treatment for typhoid fever. However, S. typhi has increased resistance to second-line antibiotics, so azithromycin has become an alternative treatment for the typhoid fever. This systematic review assessed the effectiveness of azithromycin and ciprofloxacin against typhoid fever in adults. This research used the PRISMA protocol with predefined Pubmed, Proquest, and EBSCO keywords. After removing duplicates and selecting studies according to inclusion and exclusion criterias, 17 studies about the effectiveness of azithromycin and ciprofloxacin in typhoid fever in adults from 1988-2020 were gathered. Studies were evaluated using JBI Critical Appraisal Tools. The results showed that administration of azithromycin and ciprofloxacin for typhoid fever yields average length of fever (3.5 d and 4.2 d) and average length of stay (9.3 d and 10 d), respectively. The susceptibility of S. typhi to azithromycin was 99.9%, whereas a significant decrease in its susceptibility to ciprofloxacin was observed in 2017-2020, from 4% to 2%. Azithromycin showed better effectiveness than ciprofloxacin in treating typhoid fever in adults based on S. typhi’s susceptibility, average length of fever and average length of stay from 17 studies reviewed.